Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1120/jacmp.v12i1.3424
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of oblique tangential photon beams calculated by superposition/convolution algorithms: a Monte Carlo evaluation

Abstract: Although there are many works on evaluating dose calculations of the anisotropic analytical algorithm (AAA) using various homogeneous and heterogeneous phantoms, related work concerning dosimetry due to tangential photon beam is lacking. In this study, dosimetry predicted by the AAA and collapsed cone convolution (CCC) algorithm was evaluated using the tangential photon beam and phantom geometry. The photon beams of 6 and 15 MV with field sizes of 4×4 (or 7×7), 10×10 and 20×20 cm2, produced by a Varian 21 EX l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Although AAA can calculate dose distribution more accurately than older algorithms such as pencil beam convolution, 31 the accuracy of AAA in the present study was not sufficient for calculating superficial dosimetry in breast treatment. Chow et al 32 compared the calculation accuracy of a superposition/convolution algorithm for oblique beams with Monte Carlo calculation, and reported that both the AAA and collapsed cone algorithms cannot accurately calculate dose distribution at depths less than 2 mm. On the other hand, Chakarova et al 12 reported that the AAA calculation showed good agreement with Monte Carlo calculation, within 3%/4 mm tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Although AAA can calculate dose distribution more accurately than older algorithms such as pencil beam convolution, 31 the accuracy of AAA in the present study was not sufficient for calculating superficial dosimetry in breast treatment. Chow et al 32 compared the calculation accuracy of a superposition/convolution algorithm for oblique beams with Monte Carlo calculation, and reported that both the AAA and collapsed cone algorithms cannot accurately calculate dose distribution at depths less than 2 mm. On the other hand, Chakarova et al 12 reported that the AAA calculation showed good agreement with Monte Carlo calculation, within 3%/4 mm tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Photon beams of 6 and 15 MV (field size=4×4 cm2) produced by the Varian 21 EX linear accelerator were used in the irradiation. The dose grid was set to the minimum of 1 mm, according to the treatment planning system (22) . Depth doses along the cartilage (vertical broken line in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Polednik et al [18] investigated various TPS and found that the collapsed-cone algorithm underestimates the surface dose by 20%. Chow et al [19] studied the accuracy of superposition/convolution algorithm for oblique photon beams using Monte Carlo calculation and reported that AAA and collapsed-cone algorithms cannot accurately calculate the dose below 2 mm. In our study, dose measurements for IMRT and VMAT were made at the surface of the phantom and TPS underestimated the dose by up to 22.2%.…”
Section: Open Field Irradiation a Comparison Between Film Measurementmentioning
confidence: 99%